EXPOSURE OF THE PUBLIC OF THE LENINRGAD REGION DUE TO THE NATURAL SOURCES OF IONIZING RADIATION - O. A. Istorik; L. A. Eremina; A. N. Barkovsky; T. A. Kormanovskaya; R. R. Akhmatdinov (Радиационная гигиена)
This study is focused on the analysis of the results of the radiation-hygienic passportisation and the Joint state system of control and accounting of the individual doses of the public from natural sources of ionizing radiation in the Leningrad region. The results of the study include data on the number of measurements of the gamma-radiation dose rate in buildings and in open territories, number of measurements of volume activity and equivalent equilibrium volume activity of radon in the air in the public and residential buildings in the Leningrad region in 2007–2016 as well as the number of the assessments of the total volume alpha and beta activity and concentration of the natural occurring radionuclides in drinking water. The authors performed an assessment of the annual individual effective dose per resident of theLeningradregion. It was estimated as 3.09 mSv/year considering all the data in Regional dose databank. Natural sources of ionizing exposure contribute 92.6% to the annual effective dose to the public of the Leningrad region, that exceeds the average Russian values by 6%.